LEGAL STATUS OF AKTOR’S FOR CORRUPTION (In the Perspective of Islamic Law) - Sumarwoto Umar (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Corruption is a universal problem faced by all countries and a thorny problem that is difficult to eradicate, it is not because the problem of corruption is not only related to economic issues alone but also related to political problems, the power, and law enforcement. In Indonesia "virus" attacking corruption continues to spread in all joints of social life. Even the latest trend of corruption is no longer carried out individually by the timid and furtive but in congregation, and is regarded as a 'reasonableness'. Corruption has been entrenched in the culture of which he is religious, so that the level of corruption in Indonesia has included systemic corruption. Problems and challenges must be overcome, in particular the Islamic community who are the majority of Indonesian citizens. Ironically, the country that is predominantly Muslim and uphold the spiritual values have been ranked first as the most corrupt country in Asia and the slowest country out of the crisis than its neighbors; The tragic reality of the issue, a moral burden and responsibility that is not light. With corrupt person could collect the money in large enough quantities in a relatively short period of time. The culprit is not only high-level officials but also officials menggurita levels down even to the "top" of the people. This is illustrated by his grounded term drinking money, gas money, lubricants, administrative costs, and many other terms that actually belong to the illegal fees. In the context of the broader Islamic teachings, corruption is an act that is contrary to the principle of justice (al-`adalah), accountability (al-trust), and responsibility. Corruption with all its negative impacts that cause various distortions on the life of state and society. Is a naive if ironic fact above inflicted upon Islam as a religion professed by the majority of the population. What needs to be scrutinized here is our religious orientation that emphasizes piety-formal ritual to ignore piety and moral-social individual. Religious models like this are difficult to prevent followers from bad behaviors (corruption). This study aims to contribute ideas related to the concept of corruption and the legal status for the perpetrators of acts of corruption in the perspective of Islamic law, so that at 38 “Comparative Law System of Procurement of Goods and Services around Countries in Asia, Australia and Europe”least the subject of reflection and a warning that corruption is a sin / damned, because the resulting adverse impacts for a community and a nation very big and serious.